Ridges and riblets: Shark skin surfaces versus biomimetic models - Gabler-Smith, Molly K.; Lauder, George V. (Frontiers in Marine Science, 2022)
Shark skin has been an inspiration for biomimetic materials and structures due to its role in reducing drag and enhancing thrust, properties believed to be due to the textured surface composed of ridges on the surface of individual tooth-like scales (denticles). Attempts to replicate the hydrodynamic performance of shark skin have involved manufacturing both engineered riblets and fabrics with textured surfaces. However, there are no studies that compare the surface ornamentation of shark denticles to bioinspired materials. Using three-dimensional surface profilometry we analyzed the cross-sectional profile of the surface of shark denticles at two locations on 17 species and compared these data to values obtained from engineered structures (e.g., riblets) and competition swimsuits that are often proposed as having a comparable surface texture to shark skin. Of the variables measured, crown aspect ratio (p = 0.007), ridge height, ridge spacing, ridge aspect ratio, and ridge bumpiness (all p < 0.001) differed among the three materials. Overall, engineered riblet surfaces were very different than biological shark skin. Some of the competition swimsuit materials were more shark-like, with the fabric texture having similar height variation, but with irregular ridge spacing. Cross-sectional profile, which includes pathlength and aspect ratio in addition to ridge spacing and height, is an important feature of the skin’s surface, affecting water flow over the individual denticles, and future research will address these parameters. Quantitative 3D analysis of the surface of real shark denticle ridges enables the design of more biomimetic engineered shark skin surfaces.